2013
DOI: 10.1111/plb.12052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24‐epibrassinolide on plant growth, osmotic regulation and ion homeostasis of salt‐stressed canola

Abstract: This study evaluated effects of foliar spraying 24-epibrassinoide (24-EBL) on the growth of salt-stressed canola. Seedlings at the four-leaf stage were treated with 150 mM NaCl and different concentrations of 24-EBL (10(-6), 10(-8), 10(-10), 10(-12) M) for 15 days. A concentration of 10(-10) M 24-EBL was chosen as optimal and used in a subsequent experiment on plant biomass and leaf water potential parameters. The results showed that 24-EBL mainly promoted shoot growth of salt-stressed plants and also ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 61 publications
0
43
1
Order By: Relevance
“…EBR also affects other developmental processes, such as the germination of seeds, root and stem growth, fruit development, senescence, abscission, and maturation (Müssig, 2005;Fariduddin et al, 2014). Many studies have shown that EBR could confer resistance to plants against various abiotic and biotic stresses, such as drought stress (Yuan et al, 2010), mixed salinity-temperature stress (Hayat et al, 2010), heat stress (Kagale et al, 2007), salt stress (Liu et al, 2014), cadmium stress (Hasan et al, 2011), phenanthrene stress (Ahammed et al, 2013), and Ca(NO 3 ) 2 stress (Yuan et al, 2012). Recently, several studies demonstrated that foliar application of EBR could enhance plant tolerance to different stresses via improving photosynthetic capacity, mainly owing to an increase in the chlorophyll (Chl) content, and the up-regulation in the expression levels of various oxidative stress marker genes (Choudhary et al, 2012;Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…EBR also affects other developmental processes, such as the germination of seeds, root and stem growth, fruit development, senescence, abscission, and maturation (Müssig, 2005;Fariduddin et al, 2014). Many studies have shown that EBR could confer resistance to plants against various abiotic and biotic stresses, such as drought stress (Yuan et al, 2010), mixed salinity-temperature stress (Hayat et al, 2010), heat stress (Kagale et al, 2007), salt stress (Liu et al, 2014), cadmium stress (Hasan et al, 2011), phenanthrene stress (Ahammed et al, 2013), and Ca(NO 3 ) 2 stress (Yuan et al, 2012). Recently, several studies demonstrated that foliar application of EBR could enhance plant tolerance to different stresses via improving photosynthetic capacity, mainly owing to an increase in the chlorophyll (Chl) content, and the up-regulation in the expression levels of various oxidative stress marker genes (Choudhary et al, 2012;Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Wang et al (2012) found that BRs are likely to play a negative role in regulating Fe-deficiency-induced ferric reductase activity and Fe translocation from roots to shoots in cucumber exposure in a Fe-deficient medium. Under NaCl stress, EBL reduced the accumulation of Na + and Cl − in shoot and root of canola, and improved the ion homeostasis of K + /Na + , Ca 2+ /Na + , Mg 2+ /Na + and NO 3 − /Cl − in younger leaves and roots (Liu et al, 2014). However, the mechanism of how BRs regulate ion distribution still needs further research.…”
Section: Introductionmentioning
confidence: 98%
“…Under stress, plants produce a number of phytohormones, such as salicylic acid (SA), brassinosteroids (BRs), and abscisic acid (ABA), which play a critical role in the perception of external signals and the activation of defense mechanism within plants. Brassinosteroids, a group of naturally occurring plant steroids, have been shown to provide positive effects on the regulation of plant growth and a broad spectrum of physiological responses to abiotic stresses, such as high and low temperature stress (Mazorra et al, 2002; Bajguz, 2009), drought (Yuan et al, 2010), and salinity injury (Liu et al, 2014). For example, BRs increase thermotolerance of plants by inducing heat shock protein synthesis and gene expression for heat tolerance (Dhaubhadel et al, 2002; Dhaubhadel and Krishna, 2008).…”
Section: Introductionmentioning
confidence: 99%